2022
DOI: 10.47108/jidhealth.vol5.iss2.223
|View full text |Cite
|
Sign up to set email alerts
|

knowledge and attitude of Iraqi women in reproductive age group about risk factors in pregnancy

Abstract: Improved knowledge among women about maternal risk factors significantly reduced the likelihood of adverse events in pregnancy and childbirth. This study aimed to explore Iraqi women's knowledge and attitudes about maternal risk factors in pregnancy. A multicenter cross-sectional survey was conducted from 01 January to 31 March 2019 among women of the reproductive age (15-49 years). A convenient sampling technique using a semi-structured questionnaire was recruited to interview the sample. SPSS version 16.0 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Contrarily, seven out of ten American women of childbearing age visit a doctor at least once a year for SRH services. 33 The healthcare facility should be equipped with the tools, materials, and fundamental infrastructure needed to deliver essential medical services, and women should get the best use of them In Kunming, China, a roughly comparable study revealed low SRH awareness, signi cant unmet demand for contemporary contraception, and a high frequency of unintentional pregnancy among teens. More than half of the individuals had little knowledge of contraceptive techniques, according to the data.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, seven out of ten American women of childbearing age visit a doctor at least once a year for SRH services. 33 The healthcare facility should be equipped with the tools, materials, and fundamental infrastructure needed to deliver essential medical services, and women should get the best use of them In Kunming, China, a roughly comparable study revealed low SRH awareness, signi cant unmet demand for contemporary contraception, and a high frequency of unintentional pregnancy among teens. More than half of the individuals had little knowledge of contraceptive techniques, according to the data.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, low-risk factors include null parity, postmenopausal obesity, and a high-fat diet. Urban residence, Black race (below 45 years), older age irrespective of race, and a history of endometrial or ovarian cancer are associated with elevated risks [5,6]. Examining breast cancer risk factors is pivotal, influencing critical medical decisions for women.…”
Section: Introductionmentioning
confidence: 99%